Análise espacial das áreas úmidas da bacia do rio Caiapó, Go - Cedro, Diego Antônio Botelho de (2011)
Wetlands are complex ecosystems with Genesis, evolution and dynamic private situated in soil/water interface and relief, which has a key role in the hydrological dynamics and on biodiversity. These areas are extremely vulnerable to human actions, which are controlled by a complex natural system processes, sensitive to the effects of occupation and management techniques are not appropriate. This research has emerged on the importance of studying the humid areas of Cerrado biome, using as example the basin of the Caiapó river, one of the tributaries of the right bank of the rio Araguaia, Goiás. In the survey were identified and classified the humid areas of the basin selected, raised and classified the anthropic use classes for spatial analysis and temporal behavior of the forward to the evolution of the use and the relationship between these antagonistic classes.The images used for land-use studies and identification of wetlands were those for the years 1975, 1985, 1995 and 2009, obtained by means of the satellites Landsat MSS 1 (1975) and Landsat 5 TM (all other). Such images were referenced and mosaicadas with employment, and threaded software ENVI and classified with the Spring software for identification of areas of interest. So if you could cover the entire area of the basin of the Caiapó river were used three Landsat 5 TM scenes, being they orbit/point 223/71, 72 and 223/224/71 4 and Landsat scenes 1 MSS, the lifting of the year 1975, orbit/point 239/071/072, 239, 240 and 240/071/072. The wetlands were classified in Mata Galeria/Ciliar, Campo Limpo Úmido, Campo Sujo Úmido, Várzeas, Vereda/Buritizal, Lake and Rivers/water; the anthropic soil usage types have been classified in agriculture, grazing, urban area and preserved area. The products generated in shape format, were converted to AscII format and transported to the software metrics analysis for Fragstats landscape. This way, we obtained a database on the humid areas, containing various satellite images of the months subsequent to the rainy season (may, June and July) for these years, was also developed a methodology for identifying wetlands to this roster 1: 150,000 and, finally, the results have been achieved where reveals the predominance of Ciliary/Gallery Forest class between the humid areas in the year 2009 and also, the advancement of agricultural activities on these areas, often disregarding the environmental laws in force. The integrated use of the basic tools of remote sensing and geo-processing proved efficient for this kind of work, producing useful information for better understanding of the process of fragmentation in the area.